Post Method Pedagogy as an Alternative to Autonomous and Well Oriented Teaching Practices - Arias Coronado, Blanca Bernarda (Universidad Pedagógica y Tecnológica de Colombia, 2015)
This paper is a theoretical discussion focused on post method characteristics and parameters proposed by Kumaravadivelu (1994, 2001, 2003, 2006). Based on these considerations, the paper discusses someadvantages and shortcomings by applying the post method pedagogy. The reflective paper concludes that postmethod pedagogy is an interesting alternative to teach, but it implies a challenge for teachers since theyneed to take responsibility of their own professional development and their role as reflective and active teachers